(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
Allusion is as a main part of what majority of writers and poets use, so it’s worth defining the word as a stylistic device and term by exploring some of the issues that arise from its use in literary texts and poems. Initially though, a handy one-sentence definition might help: allusion is when a writer or the poet calls into play the work of another writer, implicitly mentioning that other writer by name. If the writer is mentioned, it becomes a reference. An allusion, therefore, is often implied and not direct, rather than being spelt out for the reader.